Sustainability in the print and packaging industry - TUTAK, DOĞAN; AYDEMİR, CEM; YENİDOĞAN, SEMİHA (My University, 2023)
In the printing and packaging industry, sustainability is defined as manufacture and practices that reflect responsibility for the environment and resources to meet the needs and expectations of future generations. In this article, raw material management, cellulose resources, industrial forests, ecological and renewable alternative fiber resources were examined in the framework of the sustainability of the printing and packaging industry. The recycling of printed materials and packaging and the effects of paper-ink types and product design in this recycling have been discussed. The effect of separation and processing at the source on the efficiency of paper recycling, economy and ecology was emphasized. The greenhouse gas emissions of solvents used in inks and cleaners, the impact on climate change, water footprint and carbon footprint issues were examined. Suggestions have been made on environmental sustainability in the printing industry, what needs to be done for a competitive production, successful optimization, minimization of waste, use of existing possibilities, recycling and evaluation of alternatives and use of clean energy.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)